Incorporação de lodo proveniente de lavanderia industrial em argila para a fabricação de tijolos - Herek, Luciana Cristina Soto (2009)
Industrial laundries generate, during washing and dyeing processes, a large amount of effluent that must be treated prior to its discharge into a receiving source. During the treatment of this effluent, a solid waste known as 'mud' is formed due to the addition of coagulation and flocculation agents, which are used to remove color from the effluent. The mud creates an environmental problem for these industries, as it contains heavy metals originated from the dyes. Therefore, this waste should not be disposed of without an appropriate treatment. The ABNT NBR 10004/04 classifies industrial solid wastes, and according to this norm the residue from the treatment of effluents from industrial laundries is not dangerous, but because of its solubility it should be treated before its final disposal. The objective of this work includes the treatment of the solid waste generated in industrial laundries using the technology of solidification/stabilization in ceramic material, aiming at a subsequent application, after quality confirmation by leaching and solubilization tests. This residue will be incorporated into clay mass, aiming at the manufacture of new construction materials. After the raw materials characterization (mud and clay mass), sealing bricks were manufactured in laboratory-scale through the incorporation of mud in clay mass in the following percentages by weight of mud: 0 (control), 5%, 10%, 12%, 15%, 16%, 20%, and 24%. Metals were analyzed by means of leaching and solubilization tests (NBR 10.005/04 and NBR 10.006/04, respectively) to check the efficiency of the solidification/ stabilization process. To verify the quality of the product as a construction material, physical tests of compression resistance (NBR 15.270-3/05) and water absorption (NBR 15.270-3/04) were accomplished. Surface analyses by scanning electron microscopy were performed to verify the compaction of the mud/clay mass mixture. The results showed that the compression resistance is inversely proportional to the amount of mud added in the manufacture of bricks, while water absorption is directly proportional to that amount of mud. The manufacture of sealing bricks in laboratory-scale is possible with up to 20% by weight of mud incorporated into the clay mass keeping the parameters set by the NBR 15270-3/05. In the leaching and solubilization tests none of the analyzed metals exceeded the maximum allowed by the norms NBR 10004/05 - Annex F and NBR 10004/05 - Annex G, showing that the product is inert. The sealing bricks were produced in full-scale by an industrial process with addition of 0 (control) and 20% by weight of mud into the clay mass. In the compression resistance and water absorption tests the results obtained with laboratory-scale bricks were again observed, with decreased resistance and increased absorption after the addition of mud into the clay mass. The bricks manufactured in full-scale showed a better retention of the metals analyzed in the leaching and solubilization tests than the bricks manufactured in laboratory-scale. Sealing bricks manufactured from the incorporation of mud into clay mass are considered inert, providing environmental benefits to mud generators.